KESAMAAN DIALEK BAHASA THAILAND (PHASA THAI; ภาษาไทย) DAN BAHASA DAYAK BENAWAN KALIMANTAN BARAT - Nikodemus Niko (Universitas Majalengka, 2020)
Language as an object of sociolinguistic studies have the power when we discuss about the cultural roots. Language is not only used as a means of speaking, but also as a means to see the line and relations of a society with people outside of their communities, culturally. Indonesia society in general a little multiplicity has a history associated with the culture of the Thai community, and vice versa. The Association of this culture can be examined in terms of the language that is part of it. This paper examines about quasi dialect between Dayak languages phasa Thai Benawan West Kalimantan, where at some language line has equation. This paper uses qualitative approach method of Sociolinguistics as blade data analysis. Between Dayak languages Benawan and phasa Thai has some words in their pronunciation is similar to the meaning of the same word, then pronounced the same as the meaning of different words as well. This dialect can be outlined at the root of language between the Dayak clumps with phasa Thai which is similar or allied.